MANAJEMEN SDI DAN PEMASARAN SYARIAH USAHA BATIK BERBASIS DIGITAL DALAM MENINGKATKAN PENJUALAN DAN KESEJAHTERAAN KELUARGA - Toni Setio Cahyono; Adib Khusnul Rois; Nurul Iman,; Ahnaf Nabil Irsyaadullah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Sharia-based digital marketing to increase batik sales and improve family welfare has been implemented since 2024. Sharia-compliant batik marketing is carried out using digital marketing platforms (TikTok Shop, Instagram, and Facebook) while prioritizing Sharia-compliant marketing. This study uses a qualitative descriptive approach through interviews, observation, and documentation. This study analyzes the application of Sharia-compliant marketing principles in digital strategies. The results show that Sakha Boutique has successfully implemented Sharia-compliant digital marketing by selling halal and thayyib products, utilizing social media for market expansion, conducting honest and transparent promotions, setting fair prices according to quality, maintaining healthy Islamic competition, and implementing product distribution based on the principle of trustworthiness. This effectively contributes to increased sales while strengthening the brand's image as an ethical business that improves family welfare.